Pengembangan Media Ajar Simple Tenses Berbasis Flipbook Digital bagi Gramource English Community (GEC) - Irawan, Bambang; Gintings, Mohammad Fajar Mediyawan (Jurnal Pengabdian Kepada Masyarakat, 2025)
English proficiency, particularly in grammar, is a crucial aspect of global communication, especially in the context of flexible and independent learning. Gramource English Community (GEC), an English learning community focused on asynchronous grammar instruction through Google Classroom and Instagram, has faced challenges due to the lack of interactive learning media to support the teaching of tenses. In response to this issue, a community service team from the English Literature Department at Universitas Pamulang developed an interactive digital flipbook-based learning media covering three types of simple tenses: simple present, simple past, and simple future. This activity was carried out using the ADDIE development model, starting from partner needs analysis, material design, visual content development, to the implementation of the learning media on the community’s platforms. The flipbook was designed to be engaging, easy to understand, and supportive of flexible learning, featuring theoretical explanations, sentence examples, and interactive exercises. Implementation was done by integrating it into Google Classroom and promoting it via Instagram, reaching participants from diverse backgrounds. Validation results from experts and user testing indicated that the flipbook is effective in improving participants' understanding of tense usage and increasing their interest in learning through a visual and interactive approach. This program not only provides a concrete solution to the partner’s problem but also contributes positively to the students’ skills development in creating technology-based learning media. Therefore, this digital flipbook serves as an innovative and relevant alternative learning tool to support asynchronous grammar instruction in the digital era.